Review paperThe photosensitivity phenomenon and its diagnostics – an update - Żmudzińska, Maria; Jenerowicz, Dorota; Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The photosensitivity phenomenon is more and more frequently observed as a clinical, diagnostic and therapeutic problem. The multiplicity of photodermatosis classifications reflect the variety of their aetiopathogeneses. In this paper, an update on diagnostic possibilities of the photosensitivity reaction is presented. The methodology, reading rules and practical implications of photopatch tests are emphasized. Phototests are a modification of patch tests with the application of UVA radiation. Currently, organic sunscreens and topical non-steroidal anti-inflammatory agents are known as clinically essential photoallergens.